Conversores CC-CC de alto ganho utilizando indutores acoplados, células multiplicadoras de tensão e capacitores comutados - Schiavon, Giordano Luigi (2022)
In order to face climate change and promote sustainable development, the techniques used to generate electricity have been improved and sometimes reinvented. Thus, the advancement of electricity generation through renewable resources such as non-fossil fuels and solar energy becomes a great ally. These sources, however, generally generate low and continuous voltages, different from the standard of energy in alternating current received for consumption in industries and also for the domestic public. To make these generated voltage levels compatible, taking into account technical and economic factors, an energy processing is necessary ensuring low cost and high efficiency. During the development of this work, two topologies of switching selfclamped converters with high gain and efficiency are presented, capable of step-up the DC levels generated by the primary energy sources to compatible levels for use in DC applications or further processing, especially to create a DC bus to enable the DC-AC conversion necessary to supply the demand of most of the current applications. In these topologies, voltage boost techniques are obtained by the use of coupled inductors with voltage multiplier cells and switched capacitors. The mathematical modeling of steady-state systems is also presented, as well as description of the operating stages of the proposed circuits, computer simulation and presentation of the results found through the practical implementation of the proposed topologies. The simulations and implementation of the prototypes are carried out for a processed power of 400 W and input and output voltages of 48 V and 400 V, respectively, so that they are compatible for use in most of current photovoltaic panels. The switching frequency adopted is 100 kHz, contributing to the reduction of volume and weight of the magnetic elements.